2008
DOI: 10.1097/01.prs.0000299922.96006.24
|View full text |Cite
|
Sign up to set email alerts
|

Wound Therapy by Marrow Mesenchymal Cell Transplantation

Abstract: In skin regeneration therapy using a marrow mesenchymal cell/artificial dermis composite graft, skin regeneration is possible with bone marrow aspiration, a minimally invasive procedure. Compared with existing skin grafting techniques, the present technique is practical and much less invasive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
177
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(183 citation statements)
references
References 33 publications
2
177
1
3
Order By: Relevance
“…[25][26][27] However, only a small number have been tested in humans and consist of MSC incorporated into a fibrin spray 10 or collagen sponge. 11 Dermal substitute of animal origin may induce inflammatory reactions. 28 Therefore, further developments are warranted to lead to more clinical studies on tissue-engineered products.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] However, only a small number have been tested in humans and consist of MSC incorporated into a fibrin spray 10 or collagen sponge. 11 Dermal substitute of animal origin may induce inflammatory reactions. 28 Therefore, further developments are warranted to lead to more clinical studies on tissue-engineered products.…”
Section: Discussionmentioning
confidence: 99%
“…The breakthrough work of Japanese doctors has demonstrated that the addition of SCs to collagen sponge may be therapeutically effective and lead to wound closure [35]. Their study involved 20 patients with extensive wounds of various etiologies: burns, deep injury wounds, infections and decubitus ulcers.…”
Section: Treatment Of Chronic Wounds and Burnsmentioning
confidence: 99%
“…Yoshikawa et al treated 20 patients suffering from non-healing wounds of various etiologies with autologous MSCs ex vivo expanded with animal or autologous sera. 75 They reported complete healing in 18 of the 20 patients, while the remaining two patients died for reasons unrelated to the transplantation of MSCs. Dash et al conducted a level 1 randomized control trial including 24 patients with non-healing ulcers of the lower limb.…”
Section: Clinical Studiesmentioning
confidence: 99%